2013
DOI: 10.1002/iub.1183
|View full text |Cite
|
Sign up to set email alerts
|

A network of interorganellar communications underlies cellular aging

Abstract: Organelles within a eukaryotic cell respond to age-related intracellular stresses and environmental factors by altering their functional states to generate, direct and process the flow of interorganellar information that is essential for establishing a pro-or antiaging cellular pattern. The scope of this review is to critically analyze recent progress in understanding how various intercompartmental (i.e., organelle-organelle and organelle-cytosol) communications regulate cellular aging in evolutionarily distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 50 publications
0
87
0
Order By: Relevance
“…[58][59][60][61][62][63][65][66][67] LCA causes age-related changes in cellular proteome Age-related alterations in the rates and efficiencies of several processes within mitochondria are known to modulate the capacity of these organelles to make and release certain molecular signals; outside mitochondria, such signals have been shown to cause changes in the rates and efficiencies of longevity-defining processes in other cellular locations. [3][4][5][6]16,20,25,31,33,56 Of note, we found that a treatment of yeast cells with LCA alters the agerelated chronology of these mitochondrial processes. 5,36,38,[68][69][70] We therefore hypothesized that LCA may impact not only the levels of numerous mitochondrial proteins but also the levels of proteins in cellular locations outside mitochondria.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 55%
See 4 more Smart Citations
“…[58][59][60][61][62][63][65][66][67] LCA causes age-related changes in cellular proteome Age-related alterations in the rates and efficiencies of several processes within mitochondria are known to modulate the capacity of these organelles to make and release certain molecular signals; outside mitochondria, such signals have been shown to cause changes in the rates and efficiencies of longevity-defining processes in other cellular locations. [3][4][5][6]16,20,25,31,33,56 Of note, we found that a treatment of yeast cells with LCA alters the agerelated chronology of these mitochondrial processes. 5,36,38,[68][69][70] We therefore hypothesized that LCA may impact not only the levels of numerous mitochondrial proteins but also the levels of proteins in cellular locations outside mitochondria.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 55%
“…The PMD regulon includes the following clusters: (1) rho 0 cluster (which is governed by Rtg2p, a sensor of an age-related reduction of mitochondrial membrane potential); 4,41,52-56 (2) S1 cluster; 4,52,54,55 (3) general TCA cycle dysfunction cluster; 4,52,53,55 (4) kgd1D, kgd2D or lpd1D cluster; 4,53-55 (5) yme1D mdl1D cluster; 4,55 and (6) afo1D cluster (which is governed by Sfp1p, a transcription activator of genes encoding cytoplasmic ribosomal proteins). 4,57 The OS regulon includes the following clusters: (1) a cluster governed by the transcription factor Yap1p, a primary determinant in the antioxidant response of yeast cells; [58][59][60][61][62][63][64] (2) a cluster governed by the transcription factors Msn2p/Msn4p, which are required for expression of numerous genes in response to thermal, oxidative and other types of stress; 56,62-65 (3) a cluster governed by the transcription factor Skn7p, which is involved in the osmotic and oxidative stress responses; [58][59][60][61][62][63][64] and (4) a cluster governed by Hog1p, a mitogen-activated protein kinase orchestrating an osmosensing signal transduction pathway in yeast. 64,66,67 It needs to be emphasized that mitochondrial proteins constituting the PMD and OS regulons exhibit 3 different patterns of the age-related dynamics of changes in their cellular levels; to underscore the existence of such differences in expression, we separated each of the PMD and OS regulons into regulons "type 1", "type 2" and "type 3" (Fig.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
See 3 more Smart Citations